Catalisadores Ni-Fe/MgAl2O4 na reforma a vapor do etanol: influência da razão molar Ni/Fe nas propriedades catalíticas - Lara, Thais Paula Nogueira (2017)
The effect of iron incorporation on the catalytic properties of Ni / MgAl2O4 for the Ethanol Steam Reforming (ESR) was studied. Samples of different Fe/Ni molar ratios were prepared by wet impregnation of MgAl2O4, synthesized by the sol-gel method. The catalysts were characterized by X-ray diffraction (XRD), temperature programmed reduction (TPR), temperature programmed desorption of ethanol, near-edge X-ray absorption spectroscopy (XANES), and photoelectric spectroscopy of X-rays. The formation of the MgAl2O4 spinel was confirmed by XDR and the NiO, Fe2O3 and NiFe2O4 phases were identified in the monometallic nickel, iron and bimetallic catalysts, respectively. In TPR it was verified that the presence of nickel altered the iron properties in the bimetallic catalysts. The catalytic tests were carried out under an atmosphere of water:ethanol and water:ethanol:H2 in the temperature range of 250 to 650 °C. Changing the drag from He to hydrogen, reduced the degree of oxidation of the samples at low temperatures and, consequently, increased the activity. The higher the iron content, the lower the activity at low temperatures. The results of XANES indicated that a restructuring of the Ni-Fe particles occurs during the RVE. After the reduction, Ni-Fe alloy formation is obtained, with increasing temperature Fe migrates to the surface and is oxidized to FeO. The intensity of this reconstruction depends on the Fe/Ni ratio and the composition of the reactants, being more intense in the reaction without H2. Among the catalysts analyzed, 8Ni-5Fe was the most stable and selective to hydrogen gas during the ESR, presenting a lower carbon formation